Original paperEFFECT OF AEROBIC EXERCISE, RESISTANCE TRAINING OR COMBINED TRAINING ON GLYCAEMIC CONTROL AND CARDIO-VASCULAR RISK FACTORS IN PATIENTS WITH TYPE 2 DIABETES - Yavari, A.; Najafipoor, F.; Aliasgarzadeh, A.; Niafar, M.; Mobasseri, M. (Biology of Sport, 2012)
Physical activity has been proven as a useful intervention for prevention and treatment of type 2 diabetes mellitus (T2DM). The purpose of this article was to compare the effects of aerobic exercise alone and resistance training alone as well as the combination of aerobic plus resistance training on glycaemic control, cardiovascular risk factors, and body composition in patients with T2DM. Eighty T2DM participants (37 men, 43 women), aged 33-69 years, were randomly divided in equal numbers (n=20) into one of four groups (aerobic, resistance, combined training, and control). Exercise training was performed three times per week for 52 weeks. After one year, 60 subjects (15 subjects in each group) were entered into the statistical analysis. Seventeen parameters were evaluated. Mean HbA1c showed statistically significant reductions in the three training groups. All subjects of training groups experienced improvement in postprandial glucose, blood pressure, VO2max, and muscular percentage. Furthermore, the reduced concentration of plasma triglycerides was significant in both aerobic exercise and combined training groups. Also, a significant reduction was observed in body fat percentage in resistance and combined groups. Combination of two forms of exercise training led to an additional improvement in some of the parameters such as A1c and triglycerides compared with aerobic alone or resistance training alone. In general, the reported results in previous studies were not obtained for whole lipid profile and BMI. Both aerobic and resistance training are effective interventions for the management of T2DM complications, but combined training is associated with greater positive changes.